Mobility Medicine: A call to unify hyper-fragmented specialties by abstracts sent to 2025Pdm3, and typescripts to Ejtm3, and Diagnostics - Ugo Carraro; Marie Sophie Alberty; Stephen Anton; Elena Barbieri; Ines Bersch; Bert Blaauw; Gerardo Bosco; Riccardo Forni; Massimo Ganassi; Paolo Gargiulo; Paulo Gentil; Ashraf S. Gorgey; et al. (European Journal of Translational Myology)
Mega scientific conferences increasingly suffer from the need for short and poster presentations without discussion. An alternative is to organize workshops in hotels large enough to accommodate all participants. This significantly increases the opportunities for constructive discussion during breakfasts, lunches, dinners and long evenings that can bring together experts of scientific and clinical sub-specialties and young fellows. Time for groups' discussions and new collaborations are increased so as the job opportunities for the young researchers. The Padova Muscle Days have offered in the previous thirty-five years these opportunities, which have matured into innovative and multidisciplinary results to the point that it came naturally to underline it with a neologism now included in the title of the 2025 event: “Mobility Medicine”, a discipline not yet officially recognised, that makes explicit the call for rejoining knowledges dispersed in sub-specialisations. The included program of the Padua Days on Muscle and Mobility Medicine 2025 (2025Pdm3) will be hosted at the Hotel Petrarca in Euganean Thermae (Padua, Italy) from 25 to 29 March 2025. It further testifies by listing unique Sessions that it is possible to organize valid countermeasures to the inevitable tendencies towards hyperspecialization that the explosive increase in scientific progress brings with it. Furthermore, the European Journal of Translational Myology and Mobility Medicine (Ejtm3) will accept typescripts on results presented at the 2025Pdm3, together with the Special Section: New Trends in Musculoskeletal Imaging of the MDPI (Basel) Journal Diagnostics, because diagnosis is essential to prevent, manage and follow-up not only neuro-metabolic-muscular disorders, but the unavoidable physiologicical decay of performances in early and late aging. Hoping many others share our dreams, we look forward to meeting you at 2025Pdm3 conference.